2003
DOI: 10.1177/02610183030233002
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of Approaches to the Concept of Social Identity in Social Policy

Abstract: This article seeks both to highlight a current imbalance in approaches to social identity in social policy, and to make suggestions as to how this might be redressed in future work employing the concept.The concept of identity and specifically social identity is increasingly employed in the discipline of social policy as a theoretical device with which to bridge the individual/social divide. The argument presented here suggests that the concept is however, unevenly deployed in policy analysis and, therefore la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…Service providers were also, to some extent, involved in this process as well. Indeed, it has been suggested that there is a need to focus on the agency of professionals and not just the welfare user (Hunter, 2003). It appeared that many service providers had seen their roles develop since dispersal began, often taking on multiple roles, in terms of advising and supporting around issues that perhaps were not part of their original remit.…”
Section: Resultsmentioning
confidence: 99%
“…Service providers were also, to some extent, involved in this process as well. Indeed, it has been suggested that there is a need to focus on the agency of professionals and not just the welfare user (Hunter, 2003). It appeared that many service providers had seen their roles develop since dispersal began, often taking on multiple roles, in terms of advising and supporting around issues that perhaps were not part of their original remit.…”
Section: Resultsmentioning
confidence: 99%
“…Some research has implicitly or explicitly viewed health and social care practitioners as rather uni-dimensional in their adherence to dominant policy discourses (see Hunter, 2003 for an in depth discussion of this point). In contrast, we draw on research suggesting that practitioners often work within a space of creative tension that respects managerially-based demands, whilst also incorporating alternative understandings shaped by experiential knowledge and by social identities within the 'private' sphere (Hoggett, Mayo & Miller, 2006).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…For Bensimon and Marshall (2003), policy science can never uncover power dynamics or the gendered, classed, and 'raced' impact of supposedly neutral policies. Furthermore, Hunter (2003) argues, there is a need to focus on the identities and social locations of policymakers alongside the subjects/objects of policy.…”
Section: Methodsmentioning
confidence: 99%